QUALITY OF SENGKUBAK LEAF SIMPLICIA FROM VARIOUS STAGE OF MATURITY AND DRYING METHODS - SEMBIRING, Bagem Br; FULAZZAKY, Muhammad Ali; HARIS, Helmi; RACHMAT, Ridwan; HISTIFARINA, Dian; SIREGAR, Tika Hafzara; TRIYONO, Agus (Food Science and Technology, 2025)
The sengkubak plant, especially its young leaves, has been used by the Dayak tribe as a food flavoring for generations. Apart from being a flavoring, it can also be a medicinal ingredient. The sengkubak plant has not been cultivated, it grows wild in the forest. The research aims to determine the effect of the drying method and the level of leaf maturity in producing quality simplicia with broad benefits. Parameters consisted of dry weight yield, moisture content, colour, protein content, antioxidant activity, and leaf chemical compounds. The highest dry weight yield of sengkubak leaves ranged from 25.94-27.10%, the lowest moisture content was 6.79-7.05%, and the smallest IC50 value, namely 249.19-250.50 ppm, was found in the oven drying method.The highest protein content ranged from 20.94-22.45% in young and medium leaves. The results of chemical components in sengkubak leaves, the wind-drying method detected 21 chemical compounds in young leaves, 21 in mature and 17 in old leaves. The method para-para 11 components in young leaves, 15 in mature and 24 in old leaves. Meanwhile, with the oven, young leaves had 15 chemical compounds, medium 17 and old leaves had 12 chemical compounds. The level of leaf maturity and drying techniques influence the quality of sengkubak leaf simplicia. Quality sengkubak leaves are young and mature that are air-dried and placed on a rack covered with a black cloth under the sunlight.. The SEM results show that the powder morphology of young and old leaves is round and hollow, while mature leaves are rod-shaped. Meanwhile, the TGA results show that the heating temperature that can leave around 50% of the sample is around 364.04-370.29°C with a heating time of around 33.90-34.52 minutes, there is no difference between young, medium, and old leaves.